Why prediction markets work: The role of information acquisition and endogenous weighting - Christoph Siemroth (University of Mannheim, Department of Economics, 2014)
In prediction markets, investors trade assets whose values are contingent on the occurrence of future events, like election outcomes. Prediction market prices have been shown to be consistently accurate forecasts of these outcomes, but we don't know why. I formally illustrate an information acquisition explanation. Traders with more wealth to invest have stronger incentives to acquire information about the outcome, thus tend to have better forecasts. Moreover, their trades have larger weight in the market. The interaction implies that a few well-situated traders can move the asset price toward the true value. One implication for institutions aggregating information is to put more weight on votes of agents with larger stakes, which improves on equal weighting, unless prior distribution accuracy and stakes are negatively related.
urn:nbn:de:bsz:180-madoc-374527
Keywords: D83; D84; G13; 330; Information Acquisition; Information Aggregation; Forecasting; Futures Markets; Prediction Markets